Sociocultural transitions and developmental impacts in the digital economy of impact sourcing. (26th May 2017) - Sandeep, M.S.; Ravishankar, M.N.
Abstract: Impact sourcing (ImS) is the practice of bringing digitally enabled outsourcing jobs to underprivileged communities. While such jobs are attractive and improve life chances, situated ImS employees face the difficult task of transitioning from their traditional communities to the relatively modern ImS workplace. These transition experiences expose them to a variety of work‐life challenges and, at the same time, serve as occasions for development. This paper draws on an inductive qualitative study of an up and coming Indian ImS company and explores how ImS employees experience sociocultural transitions and realize developmental impacts. The findings suggest that compartmentalization and integration strategies help ImS employees manage boundaries arising from the contrasting cultural expectations of the community and the workplace. Impact sourcing employees respond to sociocultural transition challenges in the workplace through a series of cognitive adjustments, which involves the creation of fictive kinships, job crafting, and experimenting with provisional selves . Furthermore, the analysis shows how intense engagement with sociocultural transitions can lead to the development of crucial individual and collective capabilities. In closing, a model of capability development of ImS employees is outlined, and the implications for ImS companies are discussed.